2014
DOI: 10.1007/s10600-014-1069-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition of Malus baccata Fruit

Abstract: Natural populations of Malus baccata (L.) Borkh. occur in eastern Siberia and Primorsky Krai in addition to the Mongolian People's Republic and northern China. The plant grows in river valleys, on islands, and on steppes and shrubsteppes. It is an exceptionally frost-resistant representative of the genus. The trees can withstand temperatures as low as -50°C.Polyphenolic compounds, primarily flavonoids contained in apples, are known to be involved in the regulation of human physiological functions. The qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
1
6
2
Order By: Relevance
“…The moisture content in Malus baccata fruits was 75.53±0.34%, while the total dry weight was 24.47%. Our values for dry matter were higher than finding of Hallmann et al (2011) and it was in accordance with reported values for cultivated varieties (approximately 24%) and lower than naturally growing Siberian representatives (approximately 30% of the raw mass) (Rudikovskaya et al 2014). In our study, moisture content in Malus baccata fruits collected from UK was close to values reported for Indian representatives -78.53% (Kumari and Dhaliwal 2017).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The moisture content in Malus baccata fruits was 75.53±0.34%, while the total dry weight was 24.47%. Our values for dry matter were higher than finding of Hallmann et al (2011) and it was in accordance with reported values for cultivated varieties (approximately 24%) and lower than naturally growing Siberian representatives (approximately 30% of the raw mass) (Rudikovskaya et al 2014). In our study, moisture content in Malus baccata fruits collected from UK was close to values reported for Indian representatives -78.53% (Kumari and Dhaliwal 2017).…”
Section: Resultssupporting
confidence: 91%
“…The fruit is known by the name of sheed palek, palanu and palek locally in India (Kumari and Dhaliwal 2017). Тhis plant is widely distributed throughout the world, as its natural populations occur in Asia (mainly Russia -eastern Siberia, Primorsky Krai; Mongolia, Northern China, India, especially in Himachal Pradesh) and cultivated varieties grown in Europe and China (Hallmann et al 2011;Rudikovskaya et al 2014;Kumari and Dhaliwal 2017;Dadwal et al 2018). Malus baccata was widely grown as a popular ornamental tree in the gardens and parks of Europe, North America and South America (Yoshizawa et al 2004;Aladedunye and Matthäus 2014;Kumari and Dhaliwal 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations